Longitudinal study of symptom severity and language in minimally verbal children with autism - Thurm, Audrey (J Child Psychol Psychiatry, 2014)
BACKGROUND: A significant minority of children with autism spectrum disorder (ASD) are considered “minimally verbal” due to language development stagnating at a few words. Recent developments allow for the severity of ASD symptoms to be examined using Autism Diagnostic Observation Schedule (ADOS) Social Affect (SA) and Restricted and Repetitive Behaviors (RRB) domain severity scores. The aim of the current study was to explore language outcomes in a cohort of minimally verbal children with autism evaluated through the preschool years and determine if and how ASD symptom severity in core domains predicts the development of spoken language by age 5. METHODS: The sample consisted of 70 children with autism aged 1 to 5 years at the first evaluation who were examined at least one year later, during their fifth year of age. The ADOS overall level of language item was used to categorize children as minimally verbal or having phrase speech, and the Mullen Scales of Early Learning was used as a continuous measure of expressive language. RESULTS: At Time 1, 65% (n=47) of children in the sample were minimally verbal and by Time 2, 36% (n=17 of 47) of them had developed phrase speech. While the Time 1 ADOS calibrated severity scores did not predict whether or not a child remained minimally verbal at Time 2, change in the SA calibrated severity score (but not RRB) was predictive of the continuous measure of expressive language. However, change in SA severity no longer predicted continuous expressive language when nonverbal cognitive ability was added to the model. CONCLUSIONS: Findings indicate that the severity of SA symptoms has some relationship to continuous language outcome, but not categorical. However, the omnipresent influence of nonverbal cognitive ability was confirmed in the current study, as the addition of it to the model rendered null the predictive utility of SA severity.